Pengaruh Faktor-Faktor Internal Mata Kuliah Bordir dalam Meningkatkan Motivasi Berwirausaha bagi Mahasiswa Program Studi Desain Mode Aks Ibu Kartini - Mien Zyahratil Umami; Romadhona Chusna Tsani (Garina, 2026)
Embroidery is one of Indonesia’s traditional craft arts that has developed over time and continues to attract people from various social backgrounds. Embroidery techniques are commonly applied to fashion products as well as household items. The diversity of embroidery motifs and techniques provides aesthetic value and uniqueness to each product, making embroidery an important element in the development of the fashion industry. This opportunity can encourage students of the Fashion Design Program at AKS Ibu Kartini to develop their entrepreneurial potential through creativity in manual embroidery. This study employed a quantitative approach using multiple linear regression analysis as the data processing technique to determine the influence of internal factors on the entrepreneurial motivation of Fashion Design students at AKS Ibu Kartini. The research sample consisted of 65 respondents. The findings revealed that, simultaneously, the four independent variables had a significant effect on entrepreneurial motivation, with a coefficient of determination (R²) value of 0.910. This indicates that 91% of the variation in entrepreneurial motivation can be explained by technical knowledge (X1), technical skills (X2), creativity and innovation (X3), and entrepreneurial mindset (X4), while the remaining 9% is influenced by other factors outside this study. Partially, variables X1, X2, and X4 showed a positive and significant effect on entrepreneurial motivation, whereas X3 demonstrated a negative and significant effect. This finding indicates that creativity without market orientation may reduce students’ motivation to engage in entrepreneurship. The implications of this study emphasize the importance of improving students’ knowledge, skills, and entrepreneurial mindset. Furthermore, proper guidance is needed to ensure that students’ creativity and innovation are aligned with market demands in order to optimally enhance entrepreneurial motivation.